Fator de decisão na adoção de um sistema de micro-cogeração de energia a gás natural :um estudo em Hotéis três estrelas - Câmara, Paulo Roberto da (2006)
The natural gas perform a essential paper, not only in primary sectors of energy, but also in others sectors of economy. The use natural gas will have expansion in Brazil, motivated by governmental decision to increase the participation of this fuel in the Brazilian energy matrix from 4% to 12% up until 2010. in order to reach the objective related to increase the consumption of natural gas in the energy matrix and to propose solutions to attend the electric requirements of heart and refrigeration, using natural gas as primary power plant. This thesis has a main objective to analysis the perception of businessmen of hotel sector about the feasability of investment with micro-cogeneration system by natural gas in their hotel in turistic sector, in Natal/RN. It s show a case for the hotels selected analyzing the actual knowledge of businessmen about alternative of new technology in generation of owner energy. There was make a interview using a standard form researching information about this topic. In this interview has shown 4 (four) canaries for businessmen with different configurations of investment in micro-cogeneration. Two of this canaries uses the project finance like option to make fasible this projects. The resulteis showed who businessmen has insecurity to make decision to put in office alone, or with a local company, and perhaps with a national company to perform for a alternative energy system, justifying, the alone feasability and without information by local businessmen. Apart from that, they are receptive for a option to put in office in micro-cogeneration configured in the settings using project finance